(3QSGdI eNJUQI aj eYQaI GSJNQGL CYeGd Gddjd hGdfgGQ ef GdQHY GdeLjHs - (3jMj Hf eMeO Hf NWGH GdeGdcjs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI hHYO agPg ebOeI eNJUQI aj eYQaI GSJNQGL GYeGd Gddjd hGdfgGQ ef QHY GdOGFQI GdeSeGI HQHY GdeLjH LYdJgG hSjdI ddeHJOF aj Yde GdejbGJ s
(3BNQgG (B:s
(3ef BNQ GdehLhO hgh GdNW GdKGfj YTQ ef GYOGO eLjH GdJeGe GdeSJhjI hYf cd ef GdNWjf GdePchQjf s
(3Vef eLehY , JQJjHgG (B: 9s
(3HgG fXGe GdJYbjHIs
(3GNJUQgG ef QSGFd SHW GdeGQOjfj hZjQg hjJdhgG LOGhd aj GdejbGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs